Removal of saturated aliphatic hydrocarbons (gasoline components) from air via bacterial biofiltration - Paca, Jan; Halecky, Martin; Vanek, Tomas; Kozliak, Evguenii; Jones, Kim (Journal of environmental science and health. Part A, Toxic/hazardous substances & environmental engineering, 2010)
Two-stage biofilters (using perlite and granular activated carbon, GAC, as packing materials) were used for the removal of several linear, branched, and cyclic C(5)-C(8)saturated aliphatic hydrocarbons from air, both as individual chemicals and in mixtures. The acclimation of biofilters from styrene to n-heptane was complete in 14-18 days. The substrate switch resulted in significant changes in pH and microbial composition of biofilters. Subsequent experiments were conducted under steady state conditions at a constant EBRT of 123 s and near-neutral pH, assuring the predominantly bacterial (as opposed to fungal) biofilter population. n-Heptane was removed with consistently high, 87-100%, removal efficiencies (RE) for up to 16 g x m(-3) x h(-1) critical substrate loads in the perlite biofilter, while n-hexane and n-pentane exhibited significantly lower RE under similar conditions. The REs for iso-octane and cyclohexane were less than 10% under similar loads; n-heptane biodegradation was consistently ca. 10% lower in the presence of iso-octane than in its absence. The GAC biofilter showed a significantly lower efficiency than the perlite biofilter (the critical load, yielding RE > 90%, was only 5 g x m(-3) x h(-1) for n-heptane). Evidence obtained indicates that the rate limiting step for mixed culture biofiltration of aliphatic hydrocarbon mixtures is biodegradation rather than mass transfer.
Keywords: heptany; biodegradace; benzin; Filtration; filtrace; Heptanes; biofilmy; Biodegradation, Environmental; Gasoline; Bacteria; Hexanes; hexany; Biofilms